The contour method for residual stress determination applied to an AA6082-T6 friction stir butt weld - Richter-Trummer, Valentin (2014)
Residual stresses parallel to the welding direction on a cross-section of a 3 mm thick friction stir butt-welded aluminum alloy AA6082-T6 plate were determined using the contour method. A full contour map of longitudinal residual stresses on a weld cross section was determined in this way, revealing detailed information on the residual stress distribution in the inside of a friction stir weld, especially in the nugget zone. The typical M-shape, usually described for the residual stress distribution in friction stir welds, was found. The maximum residual stresses are below the yield strength of the material in the shoulder region and, outside of the welding region, low tensile and compressive residual stresses are responsible for the necessary stress equilibrium on the plane of interest. A comparison was made with the established incremental hole drilling technique on an equivalent plate for validation and good agreement of both techniques was obtained. The distribution, as well as the magnitude of the residual stresses measured by both techniques, is very similar, thus validating both the experimental and numerical procedures used for the contour method application, presented and discussed in the present paper.